Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/jobm.201300311
|View full text |Cite
|
Sign up to set email alerts
|

Production of AI‐2 is mediated by the S‐ribosylhomocystein lyase gene luxS in Bacteroides fragilis and Bacteroides vulgatus

Abstract: Quorum sensing is a cell-cell signaling mechanism based on cell density and that involves the production of hormone-like molecules called autoinducers (AI). One of the most studied AIs has been termed AI-2, and its biosynthesis requires the enzyme encoded by luxS. We have previously described for the first time that Bacteroides species can produce molecules with AI-2 activity. In this study, we focus on the detection of luxS and its activity as the AI-2 synthase in Bacteroides species. The strains Bacteroides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…and Prevotella spp. (shown in Table 1) were presumed to be xylanolytic because of the presence of genes encoding xynalases in their genome (Antunes et al 2005;Lukas et al 2008;Peixoto et al 2013), and strains of Bacteroides spp. and Prevotella spp.…”
Section: Results and Discussion Detection Of Luxs Gene Sequencesmentioning
confidence: 99%
“…and Prevotella spp. (shown in Table 1) were presumed to be xylanolytic because of the presence of genes encoding xynalases in their genome (Antunes et al 2005;Lukas et al 2008;Peixoto et al 2013), and strains of Bacteroides spp. and Prevotella spp.…”
Section: Results and Discussion Detection Of Luxs Gene Sequencesmentioning
confidence: 99%
“…Interestingly, E. coli is able to intercept extracellular AI-2 produced by other bacterial species in vitro (Peixoto et al, 2014). As the microbiota produces AI-2 like molecules (Mitsumori et al, 2003), it is possible that Enterobacteriaceae can utilize interspecies signaling in the gut.…”
Section: Multidirectional Signaling In the Gut And Effect On S Typhimentioning
confidence: 99%
“…It has recently been demonstrated that Bacteroides species can produce AI-2 like molecules [ 181 ], and heterologous expression of Bacteroides luxS orthologues can complement AI-2 production in E. coli [ 182 ]. As members of the intestinal microbiota produce AI-2, it is not inconceivable that members of these dense communities exploit LuxS-based signaling to modulate gene expression and community phenotypes.…”
Section: Multidirectional Chemical Signaling Within the Gastrointementioning
confidence: 99%